If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
2*y = y/10 // - y/10
2*y-(y/10) = 0
19/10*y = 0 // : 19/10
y = 0
y = 0
| -10d-2=-8d+10-5d | | 5x+2+1=11 | | -2p+10-8p=3-9p | | f+8=-8-f | | 2x^3+6x^2+1=0 | | 7g=9 | | 5(x+6)+3(-x+8)=36 | | 272=3x+y | | 7+5f=19+2f | | 12+x-5=7*4-10 | | 5x-3(x-4)=-9+4x+11 | | 3(x+35)+4(x+35)=7 | | 24=-2(x-9) | | 3(5x-52)=2(x+26) | | 3x-24+3x+9=97-13x | | 4(5x+85)=3(x+34) | | -4x+9=-2x+17 | | 50=5p+5 | | 3-6x=9-9x | | -2.1x+4.7=y | | 5(v-8)=-10+5v | | 6z-1=4z+3 | | S=5t+5t^2 | | 11.2+3y=20.2 | | ln(7x^2)=12 | | 6i/-3i | | 6y+30=-3(y-1) | | 11.4+3y=20.2 | | 7b-52=6b-57 | | 8(u-6)=4u-16 | | 6x-34=2(x-3) | | 272=3x |